АBC-аналіз дохідності факультетів Східноєвропейського національного університету імені Лесі Українки - Тоцька, Олеся Леонтіївна; Тоцкая, Олеся Леонтьевна; Totska, Olesia Leontiivna (Національна академія керівників кадрів культури і мистецтва, 2018)
За допомогою ABC-методу визначено групи A, B, C факультетів Східноєвропейського національного університету імені Лесі Українки залежно від показників надходжень від плати за навчання бакалаврів і магістрантів першого курсу. Дослідження проведено на основі даних приймальної комісії цього ВНЗ за 2017 рік. С помощью ABC-метода определены группы A, B, C факультетов Восточноевропейского национального университета имени Леси Украинки в зависимости от показателей поступлений от платы за обучение бакалавров и магистрантов первого курса. Исследование проведено на основе данных приемной комиссии этого вуза за 2017 год. Определено: по показателю дохода от обучения первокурсников-бакалавров 46,67 % факультетов принесут 76,75 % поступлений университета; по показателю дохода от обучения первокурсников-магистрантов это соотношение составляет 46,67 / 77,71; по показателю совокупного дохода от учебы всех первокурсников 53,33 % факультетов принесут 73,77 % поступлений университета. Using the ABC-method, groups A, B, C of the faculties of Lesya Ukrainka Eastern European National University depending on the income from tuition fees of undergraduate and graduate students in the first year are defined. The research was conducted on the basis of the data of the admission commission of this university for 2017. Determined: according to the income from the study of freshmen-bachelors 46,67 % of the faculties will bring 76,75 % of the university’s revenues; according to the income from the study of freshmen-magistrates this ratio is 46,67 / 77,71; on the indicator of the total income from the study of all freshmen 53,33 % of the faculties will bring 73,77 % of the university’s revenues.
АBC-анализ доходности факультетов Восточноевропейского национального университета имени Леси Украинки
ABC-analysis of the efficiency of faculties of Lesya Ukrainka Eastern European National University
Keywords: ABC-аналіз; Східноєвропейський національний університет імені Лесі Українки; факультет; бакалавр; магістр; освітня програма; плата за навчання; ABC-анализ; Восточноевропейский национальный университет имени Леси Украинки; факультет; бакалавр; магистр; образовательная программа; плата за обучение; ABC-analysis; Lesya Ukrainka Eastern European National University; faculty; bachelor; magister; educational program; tuition fee